Inhibited cavitation in lanthanum-doped tungsten under multiple melt exposures in GLADIS and ASDEX Upgrade - Yue Yuan; Ying Qin; Karl Krieger; Henri Greuner; Bernd Böswirth; Hanqing Wang; Mengchong Ren; Long Cheng; Guang-Hong Lu; ASDEX Upgrade Team (Nuclear Fusion)
Melt ejection and melt motion of tungsten (W) as a plasma-facing material due to accidental thermal overload events are primary concerns for ITER and DEMO. Previous experiments have revealed that W-1 wt.% La _2 O _3 is an effective material for suppressing cavitation under a single pulsed heat load (Yuan et al 2014 Nucl. Fusion 54 083026). To further investigate this effect, both W and W-1 wt.% La _2 O _3 (WL10) were subjected to multiple melt exposures in the high heat flux facility GLADIS and the tokamak ASDEX Upgrade (AUG). In GLADIS, H/He high-power neutral particle beams were used, with a total energy density of 41–50 MJ m ^−2 per pulse, adjusted by the pulse duration. In AUG, eight ELMing H-mode deuterium (D) plasma discharges (#37680–87) were employed with samples exposed by the divertor manipulator DIM-II. The results revealed that the surface and cross-sectional morphologies of the resolidified melt layers are similar in both GLADIS and AUG. The pure W samples exhibited pronounced cavitation, with numerous spherical voids in the resolidified layer. In contrast, the WL10 samples developed an undulating surface morphology with a dense resolidified layer at the top, free of spherical voids and lanthanum particles, indicating sustained cavitation suppression even after La _2 O _3 had vaporized from the top surface during previous melting. This suppression effect is likely primarily due to the formation of the undulating surface, which exposes the still La _2 O _3 -rich deeper material regions. The La _2 O _3 particles participated in subsequent melting cycles, continuously preventing cavitation. Additionally, we compared D retention in W and WL10 samples subjected to the eight D plasma discharges in AUG. D retention was significantly reduced from 2.5 × 10 ^21 to 4.4 × 10 ^19 D m ^−2 for W and slightly decreased from 1.5 × 10 ^21 to 1.2 × 10 ^21 D m ^−2 for WL10 when comparing unmolten and molten samples. Overall, multiple melting experiments in both GLADIS and AUG confirm that W-La _2 O _3 is a good cavitation-resistant material, effectively suppressing cavitation in W melt.